The applications of energy regeneration and conversion technologies based on hydraulic transmission systems: A review. (1st February 2020) - He, Xiangyu; Xiao, Guangxin; Hu, Bili; Tan, Lisha; Tang, Hongbin; He, Shanghong; He, Zhiyong
Graphical abstract: Hydraulic transmission systems (HTSs) are widely used in various industrial fields. With the increase in research on renewable energy and energy-saving technologies, energy regeneration and conversion (ERC) technologies based on HTSs, including potential energy regeneration, braking energy regeneration, vibration energy acquisition and power take-off (PTO), have attracted increasing attention. This review will comprehensively demonstrate the current status of ERC technologies based on HTSs in the application fields of construction machinery, hydraulic vehicles, regenerative suspensions and wave energy converters (WECs). Highlights: Energy regeneration and conversion technologies based on HTSs are analyzed. Four main application fields are comprehensively reviewed. Efficiency, structures and key technologies of applications are compared. Potential research directions and application prospects are proposed. Abstract: Hydraulic transmission systems (HTSs) are widely used in various industrial fields. With the increase in research on renewable energy and energy-saving technologies, energy regeneration and conversion (ERC) technologies based on HTSs, including potential energy regeneration, braking energy regeneration, vibration energy acquisition and power take-off (PTO), have attracted increasing attention. First, this review briefly explains the main concepts of ERC technologies based on HTSs and applications; then their working principles are analysed. As the main content of this review, the current status of ERC technologies based on HTSs in the application fields of construction machinery, hydraulic vehicles, regenerative suspensions and wave energy converters (WECs) are comprehensively analysed, compared and discussed. Finally, ERC technologies based on HTSs are prospected from the aspects of hydraulic system component optimization, all-electric power system integration and potential applications. This review is expected to provide readers with a comprehensive and clear understanding of ERC technologies based on HTSs through a detailed overview of their application, which will provide an important reference for further research and potential applications in this field.